Reverse-transcription loop-mediated isothermal amplification and alternative protocols for lower cost, large-scale COVID-19 testing: lessons from an emerging economy - Segura Ulate, Ismael (2022)
Introduction: Most successful cases of COVID-19 pandemic mitigation and handling have relied on extensive reverse-transcription quantitative polymerase chain reaction (RT-qPCR). However, many emerging economies have struggled with current molecular testing demands due to economic, technical and technological constraints. Objective: To define a potential diagnostic protocol to increase testing capacity in current and post-pandemic conditions. Methods: We reviewed the literature, patents and commercial applications, for alternatives. Results: We found a good potential in saliva samples, viral inactivation and quick RNA extraction by heating; the use of an isothermal technology such as loop mediated isothermal amplification (LAMP) and naked eye test-result visualization by in-tube colorimetry or turbidity. Conclusions: Saliva samples with quick RNA extraction by heating and colorimetric LAMP are promising options for countries with economic and infrastructure limitations.